Programming in C#.Net - Bradley, Julia Case; Millspaugh, A.C. (Anita C.) (2004)
With Microsoft's recent release of their Visual Development Studio (Visual Studio .Net) a new programming language has been introduced. The new language is C# .Net. "Programming in C# .Net" has been written by the successful author team of Bradley and Misspaugh, who write our Visual Basic books. Therefore, the book maintains the strong pedagogy that has been used to teach students how to program. This book assumes no prior knowledge of programming and it incorporates basic concepts of programming, problem solving and programming logic and design techniques to teach students a mastery of C# .Net at an introductory level.